Nomenclatural status of the ‘pocketknife fly’: Stomoxoides Schaeffer, 1766 (Diptera: Conopidae) - Evenhuis, Neal L.; Pape, Thomas (Zootaxa, 2014)
The nomenclatural status of the genus Stomoxoides Schaeffer, 1766 is discussed and a timeline of usage is given. The name is shown to be available and date from Schaeffer’s 1766 work, and by invoking Article 70.3 of the ICZN Code, the type species of Stomoxoides is fixed as Conops ferrugineus Linnaeus, 1761, misidentified as Conops testacea Linnaeus, 1767 in the fixation by subsequent monotypy as proposed by Linnaeus in 1767. Stomoxoides is thereby synonymous with Sicus Scopoli, 1763 as originally proposed by Yeats in 1773.